Prevention and Health Assurance From the point of view of the sage Seyed Ismail Jorjani and its comparison with the recommendations of the World Health Organization - Mohammad Reza Ajam; Mahboubeh Ismaili; Hassan Shadpour (Golestan University of Medical Sciences, 2022)
Background: The study of the views of past Iranian scholars to get out of health problems is one of the suggestions of the scientific community, especially researchers in the field of health and traditional medicine in Iran. In the work of Hakim Seyyed Ismail Jorjani, the Khwarezmshahi reserve for maintaining and ensuring the health of prevention as an essential set has been emphasized as a principle and in this research has been considered by comparing the recommendations of the World Health Organization. Methods: Due to the interdisciplinary nature of the subject, first of all, sources and references about medical history, especially Khwarazmshahi reserve book and related materials are identified on the World Health Organization website and articles in the field of medicine and traditional medicine of Iran with related keywords in Google, Google Scholar, Iran Dock, Elsevier databases. The necessary data were studied, categorized and analyzed using a descriptive-analytical method, and the findings were compared with the texts of the health field, especially the World Health Organization, regarding the relationship between the recommendations of this organization and the theories of Hakim Jorjani of the 5th and 6th centuries AH. The importance of prevention and health assurance was discussed. Results: The mean score of safety culture increased significantly from 141.19±16 to 147.93±14.05 after the intervention (P<0.001). Error reporting at the center also increased significantly after the intervention (P<0.001). Conclusion: A comparative study of Hakim Jorjani's point of view and the recommendations of the World Health Organization showed that about ten centuries ago the most important and effective way to maintain and ensure preventive health was considered in accordance with the six principles of health.